A Prototype for Mobile Application of Garbage Quantification using Mask R-CNN - Venugopal, B; Chakravarthy, L S; Praveen, L; Dwivedi, Ashish Kumar (International Journal of Computer Sciences and Engineering, 2025)
In cities especially some areas have garbage regions, So people are affected by several health issues. The main problem is authorities will not clean on time due to lack of information. Sometimes, authorities have also highly impossible to track these areas. Garbage quantification is an important step in improving the cleanliness of the cities. This paper presents one mobile application for garbage images with GPS locations to send authorities directly. When the user clicks the garbage image using through this app, then it will send that image to the server for automatic garbage detection with quantification by using the deep learning in computer vision techniques. Convolutional Neural Network (CNN) algorithms will be used to garbage detection with quantification in an image for accurate results.